Analysis of changes in heart rate variability after prolonged ultra-high plateau residence in young healthy population: a cross-sectional study - Zhang, Hongyang; Liu, Hao; Gong, Meiting; Ye, Xianglin; Wang, Peng; Li, Meiling; Yang, Haixia; Pei, Haifeng (Frontiers in Physiology, 2025)
ObjectiveThis study aims to investigate changes in the autonomic nervous system (ANS) by analyzing the characteristics of heart rate variability (HRV).MethodsA portable 3-lead dynamic electrocardiogram monitoring device was used to collect HRV data from the participants. Based on the inclusion and exclusion criteria, a total of 52 volunteers from the Xinjiang Hetian area (ultra-high plateau group, approximately 5300 m altitude) and 56 volunteers from the Sichuan Chengdu area (plain group, approximately 500 m altitude) were enrolled for the 24-hour long-term HRV data collection. A cross-sectional comparison was made between the groups in terms of various HRV time-domain, frequency-domain, and nonlinear indices. The diurnal and nocturnal variations in HRV and ANS after prolonged residence in the ultra-high plateau were further explored by dividing the day into daytime and nighttime periods and calculating the ΔHRV values. Additionally, the participants’ heart rate and sleep conditions were analyzed.ResultsCompared to the plain group, the ultra-high plateau group showed a significant reduction in overall HRV, with decreased indices of vagal activity (RMSSD, NN50, pNN50, HF, HF norm, and SD1) and increased indices of sympathetic activity (LF norm). The ANS balance indices were increased (LF/HF) and decreased (SD1/SD2), respectively. More importantly, although the diurnal and nocturnal trends of various HRV indices in the ultra-high plateau group were consistent with the plain group, the △HRV value analysis indicated that the ultra-high plateau group had increased △LF (95% CI: 10.20 to 271.60, P = 0.031) and △LF/HF (95% CI: −2.23 to −0.49, P < 0.001), and decreased △HF (95% CI: −383.10 to −35.50, P = 0.012) and △S (95% CI: −12149.47 to −2759.29, P = 0.001). Additionally, in the ultra-high plateau group, both the mean and minimum heart rates were elevated compared to the plain group (84.67 ± 1.37 vs. 73.2 ± 0.93 beats/min and 52.9 ± 1.37 vs. 47.57 ± 0.73 beats/min, respectively, P < 0.001), while the maximum heart rate was reduced (135.21 ± 1.63 vs. 144.43 ± 3.22 beats/min, P = 0.012). Furthermore, the ultra-high plateau group had a significant increase in the number of awakenings (18.27 ± 1.14 vs. 15.34 ± 1.43, P = 0.046) and the Apnea-Hypopnea Index (AHI) (20.14 ± 2.47 vs. 11.36 ± 0.76, P < 0.001).ConclusionProlonged residence in the ultra-high plateau reduces HRV, cardiac reserve capacity, and sleep quality in healthy young adults, diminishes the diurnal recovery capacity of the vagal nerve, and leads to a shift in ANS balance towards reduced vagal activity and enhanced sympathetic activity.